Banggai Language Register in Buying and Selling Interactions at Pasar Baru Banggai and Its Benefits in Indonesian Language Learning - Hasni Asis; Dakia N. Djou; Herson Kadir (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to: 1) describe the form of Banggai language register in buying and selling interactions at Pasar Baru Banggai. 2) describe the form of Banggai language register in buying and selling interactions at Pasar Baru Banggai. 3) describe the benefits of Banggai language register in buying and selling interactions at Pasar Baru Banggai for the Indonesian language learning domain. This study uses a qualitative method with a sociolinguistic approach to analyze the use of Banggai language register in buying and selling interactions at Pasar Baru Banggai. Data were obtained through observation, recording, and listening techniques. The data for this study were recordings of dialogues between sellers and buyers at Pasar Baru Banggai. The results show that Banggai language register in buying and selling interactions has a distinctive form, in the form of the use of certain vocabulary, expressions, and language variations influenced by the communication situation and the relationship between speakers. This register serves to facilitate communication, create familiarity, and streamline the transaction process. Furthermore, the use of the Banggai register also has benefits in Indonesian language learning, particularly in enriching understanding of language variations, improving sociolinguistic competence, and serving as a contextual learning resource relevant to everyday life. Thus, the Banggai register in buying and selling interactions serves not only as a communication tool but also has educational value that can be utilized in Indonesian language learning.